(3beY GdfahS hQbjI GdeCjhSs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdfGS cGfhG ai LGgdjI LgdkG hYejI YejG MJi LGA GdMb hRgb GdHGWd Ef GdHGWd cGf RghbG bGd JYGdi (B:( (3EfG CQSdfGc HGdMb HTjQG(B) s
(3BNQgG (B:s
(3ajUQYhg Ke jHbi dai GdfRY hGdYPGH eG TGA Gddg JYGdi Ke JNQL QhMg HcdGdjH hJQei ai fGQ dXi ai YPGH OGFe jbje Pdc JbOjQ GdYRjR GdYdje Je GdcJGH hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1356s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs